Effects of the combination of atomoxetine and oxybutynin in Japanese patients with obstructive sleep apnoea: A randomized controlled crossover trial. Issue 3 (2nd October 2022) - Kinouchi, Toru; Terada, Jiro; Sakao, Seiichiro; Koshikawa, Ken; Sasaki, Tsuyoshi; Sugiyama, Atsuhiko; Sato, Shun; Sakuma, Noriko; Abe, Mitsuhiro; Shikano, Kohei; Hayama, Nami; Shiko, Yuki; et al.
Abstract: Background and Objective: The possibility of combination therapy with atomoxetine (ATO) and oxybutynin (OXY) has been suggested for obstructive sleep apnoea (OSA). However, the effectiveness of this treatment remains uninvestigated in Japanese OSA patients. Therefore, we performed a randomized, crossover, phase II, single‐centre prospective trial to examine the effects of ATO–OXY therapy in Japanese OSA patients. Methods: In total, 17 OSA patients participated in this study. The effects of one night of 80‐mg ATO plus 5‐mg OXY administration were compared with those of no medication administered before sleep. The primary and secondary outcomes comprised the apnoea–hypopnoea index (AHI) and nadir SpO2, SpO2 drop time and sleep architecture, respectively. The safety endpoints included drug side effects and adverse events. Results: The values of AHI, nadir SpO2, 3% oxygen desaturation index (ODI), 4% ODI, and SpO2 drop time of <90% did not significantly differ between patients receiving ATO–OXY administration and no medication. Sleep architecture exhibited a significant change: ATO–OXY increased sleep stage N1 ( p  < 0.0001) and decreased stage N2 ( p  = 0.03), rapid eye movement ( p  < 0.0001) and sleep efficiency ( p  = 0.02). However, the subanalysis demonstrated an obvious decrease in AHI in five responder patients. Total sleep time and basal sleep efficiency tended to be lower in the responders compared with nonresponders ( p  = 0.065). No patients experienced severe adverse events or side effects. Conclusion: Overall, ATO–OXY therapy does not reduce AHI in Japanese OSA patients, although AHI was decreased in a proportion of patients. Future studies for identifying treatment response group characteristics are warranted. Abstract : This study is a prospective clinical trial of atomoxetine and oxybutynin combination therapy in Japanese patients with obstructive sleep apnoea (OSA). Unlike previous reports, no significant improvement in OSA severity was observed, although a significant change in sleep architecture was detected, suggesting a different reactivity in Japanese OSA patients. See related Editorial